ChemInform Abstract: Allyl‐Assisted, Cu(I)‐Catalyzed Azide—Alkyne Cycloaddition/Allylation Reaction: Assembly of the [1, 2, 3]Triazolo‐4, 5, 6, 7‐tetrahydropyridine Core Structure. Issue 11 (February 2016) - Deng, Xiaohu; Liang, Jimmy; Allison, Brett B.; Dvorak, Curt; McAllister, Heather; Savall, Brad M.; Mani, Neelakandha S.
Abstract: The one‐pot, three‐component synthesis of 1, 4‐disubstituted 5‐allyl‐triazoles (IV), (VI) and (VIII) is reported.